Smart factory solutions based on cellular industrial Internet of things - Shulei GONG; Kun LI; En TONG; Hongde GUO; Yi ZHOU; Ye WANG; Fei DING (物联网学报)
So far,the overall informatization level of manufacturing industry has been uneven,and there are many problems such as low intelligence and poor connectivity.First of all,with the features like low power consumption of the Internet of things,the sensor devices can be deployed flexibly to realize real-time collection and transmission of production data.Then the manufacturing execution system based on the cellular industrial Internet of things had been built,and realized the closed-loop processing of human,machine,material,method and surrounding.The industrial big data of the whole production process was modeled,analyzed and processed.The operation and maintenance cost was reduced,and the production efficiency and product quality were improved.Finally,the overall efficiency of the application was evaluated which showed that the factory capacity was improved effectively.